Financial Performance of the Luxury Market:A Study of Pre and Post Financial Crisis 2007-08 - Jain, Nidhi; Bothra, Neha (Indian Journal of Finance, 2016)
The financial crisis of 2007-08 brought down the sentiments of the investors in the market and the owners of the concerns. During a financial crisis, unemployment is assumed at the lowest, profitability sinks, investments are low, inflation is high, productivity is low, and there is a decline in demand. The entire economy endeavours for survival. Many sources have stated that the luxury market is not hit by recessionary times. The consumers of this market are assumed not to have any inclination to the market, even if bad news is pouring in. In order to check the claims of the executives and the companies and to check the resilience of the market, the present study examined the financial performance of the luxury market pre and post the financial crisis of 2007-08. The luxury market is scattered across the globe. So, the S & P Global Luxury Index was taken as a proxy of the market. It has 80 members from various countries; 2004-2013 data was collected from the Bloomberg database. Paired t -test was applied on all the measures, and the results were discussed. The results revealed that the tough time of recession proved to be difficult for the luxury market as a whole. The liquidity of the market in all the segments did not change significantly. Almost all sectors were hit by the downturn, but the textiles, apparel,&luxury goods sector proved to be the most profitable to entrepreneurs and to investors as well.